Orobanchaceae endémicas del Perú - León, Blanca (2006)
The Orobanchaceae are represented in Peru by seven genera and 48 species (Brako & Zarucchi, 1993; Stevens, 2001; Ulloa Ulloa et al., 2004), mostly parasitic herbs. Here we recognize 20 endemic taxa in Bartsia and Castilleja. These endemic taxa are found mainly in Mesoandean and Paramo regions, between 2150 and 4600 m elevation. Eleven endemic taxa have been recorded in the Peruvian System of Protected Natural Areas.